First-principles prediction of anomalously strong phase dependence of transport and mechanical properties of lithium fluoride. (15th August 2022) - Basu, Swastik; Hwang, Gyeong S.
Abstract: Solid electrolyte interphase (SEI) formation is a key factor governing the safety and performance of lithium-ion batteries (LIBs). However, still little is known about how the structure and composition of the SEI affects its stability and ion conductivity, despite its importance. Lithium fluoride (LiF) is one of the major inorganic components of the SEI, but its intrinsic role remains controversial with debatable Li-ion transport properties. Based on first-principles simulations, we present that unlike its crystalline counterpart, amorphous LiF possesses exceptionally high Li-ion conductivity at room temperature and exhibits unique mechanical properties with significant ductility-induced fracture resistance. However, the amorphous phase is found to be unstable under unstrained, ambient conditions, and exhibits a propensity to transform into the crystalline phase. This work demonstrates the possibility to stabilize the amorphous LiF structure via incorporation of heteroatoms like nitrogen (N); N-doped LiF(N) retains exceptional traits of amorphous LiF. Our findings shed light on the unique transport and mechanical features of amorphous LiF that make it of great promise as an interface material in not only LIBs but also next-generation solid-state batteries with lithium-metal anodes. Graphical abstract: Image, graphical abstract